Exercise blood pressure, cardiorespiratory fitness, fatness and cardiovascular risk in children and adolescents - Huang, Zhengzheng; Li, Xiuping; Liu, Xia; Xu, Yayun; Feng, Haixing; Ren, Lijie (Frontiers in Public Health, 2024)
Cardiovascular disease remains the leading cause of mortality on a global scale. Individuals who possess risk factors for cardiovascular disease, such as high blood pressure (BP) and obesity, face an elevated risk of experiencing organ-specific pathophysiological changes. This damage includes pathophysiological changes in the heart and peripheral vascular systems, such as ventricular hypertrophy, arterial stiffening, and vascular narrowing and stenosis. Consequently, these damages are associated with an increased risk of developing severe cardiovascular outcomes including stroke, myocardial infarction, heart failure, and coronary heart disease. Among all the risk factors associated with cardiovascular disease, high blood pressure emerges as the most prominent. However, conventional resting BP measurement methods such as auscultatory or oscillometric methods may fail to identify many individuals with asymptomatic high BP. Recently, exercise BP has emerged as a valuable diagnostic tool for identifying real (high) blood pressure levels and assessing underlying cardiovascular risk, in addition to resting BP measurements in adults. Furthermore, numerous established factors, such as low cardiorespiratory fitness and high body fatness, have been confirmed to contribute to exercise BP and the associated cardiovascular risk. Modifying these factors may help reduce high exercise BP and, consequently, alleviate the burden of cardiovascular disease. A significant body of evidence has demonstrated cardiovascular disease in later life have their origins in early life. Children and adolescents with these cardiovascular risk factors also possess a greater propensity to develop cardiovascular diseases later in life. Nevertheless, the majority of previous studies on the clinical utility of exercise BP have been conducted in middle-to-older aged populations, often with pre-existing clinical conditions. Therefore, there is a need to investigate further of the factors influencing exercise BP in adolescence and its association with cardiovascular risk in early life. Our previously published work showed that exercise BP is a potential useful method to detect adolescents with increased cardiovascular risk. Children and adolescents with cardiovascular risk factors are more likely to develop cardiovascular diseases later in life. However, previous studies on the clinical utility of exercise BP have largely focused on middle-to-older aged populations with pre-existing clinical conditions. Therefore, there is a need to investigate further the factors influencing exercise BP in adolescence and its association with future cardiovascular risk. Our previous studies, which focused on exercise BP measured at submaximal intensity, have shown that exercise BP is a potentially useful method for identifying adolescents at increased cardiovascular risk. Our previous findings suggest that improving cardio-respiratory fitness and reducing body fatness may help to reduce the risk of developing cardiovascular disease and improve overall cardiovascular health. These findings have important implications for the development of effective prevention and early detection strategies, which can contribute to improved public health outcomes.